Reduzierung der Magnetbelastung permanentmagneterregter Synchronmaschinen im dreiphasigen Stoßkurzschluss - Braun, Jochen (KIT Scientific Publishing, 2019)
This work is about the reduction of the magnetic load of a permanent magnet synchronous machine in case of a three phase short circuit. A new method is investigated in theory and tested in reality. It is applied to a permanent magnet synchronous machine with surface mounted magnets.